2020
DOI: 10.1097/aog.0000000000004125
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Sexual Activity and Function After Pelvic Organ Prolapse Surgery

Abstract: , et al. Changes in sexual activity and function after pelvic organ prolapse surgery: a systematic review. Obstet Gynecol 2020;136. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 79 publications
3
14
0
Order By: Relevance
“…Fear and self-consciousness about their bodies also affected women’s sexual lives and intimate relationships, as has been reported elsewhere [ 66 ]. Research suggests that these issues are likely a product of societal attitudes to women’s bodies rather than the anatomic features of POP [ 67 ] and that sexual function remains unchanged for many women following POP surgery [ 68 , 69 ]. Other research demonstrates an association between increased PA and improved sexual function in peri- and post-menopausal women [ 70 ], which warrants further exploration as a cost effective, low risk intervention, particularly for women with mild to moderate POP.…”
Section: Discussionmentioning
confidence: 99%
“…Fear and self-consciousness about their bodies also affected women’s sexual lives and intimate relationships, as has been reported elsewhere [ 66 ]. Research suggests that these issues are likely a product of societal attitudes to women’s bodies rather than the anatomic features of POP [ 67 ] and that sexual function remains unchanged for many women following POP surgery [ 68 , 69 ]. Other research demonstrates an association between increased PA and improved sexual function in peri- and post-menopausal women [ 70 ], which warrants further exploration as a cost effective, low risk intervention, particularly for women with mild to moderate POP.…”
Section: Discussionmentioning
confidence: 99%
“…Given the intraoperative narrowing of the genital hiatus and the fact that the measurement intraoperatively overestimates the actual genital hiatus postoperatively, the surgeon may consider re-evaluating the size of the genital hiatus after the apical suspension when deciding on the posterior compartment repair. This may be especially true for the patients who are sexually active, as overcorrection of posterior compartment can carry a significant risk of de novo dyspareunia, reported between 9–19% [ 23 , 24 ]. In our study, 50% of women were not sexually active, yet we did not find a difference in the genital hiatus size when comparing sexually active and inactive women.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction in women is frequently associated with pelvic organ prolapse (POP) [85]. In a systematic review [86], the authors found only Level 2 evidence that PFMT can improve women's sexual function, and the literature is scarce about the effect of PFMT on sexual function in women with POP.…”
Section: Sexual Bladder and Anorectal Comorbiditiesmentioning
confidence: 99%